A way of survival: A Qualitative Study of Non suicidal Self Injury Behavior in Adolescents - Su, Chunyan; Ji, Yitong; Liu, Wangxing (The Journal of Medicine, Humanity and Media, 2025)
Globally, non suicidal self injury has become a more serious social problem that affects the physical and mental health of adolescents and is very difficult to prevent and treat. This paper tries to explore the non suicidal self injury behavior of adolescents from a sociological perspective through in-depth interviews with 12 non suicidal self injury actors. On the one hand, due to the pressure of study and life, dysfunctional interpersonal relationship, peer imitation may be the external push force of non suicidal self injury behavior; on the one hand, due to personal self-determination, dysfunctional interaction with the society induces anger, impulsivity, and other emotions may be the internal drive force of non suicidal self injury behavior; on the other hand, the skin, as a kind of instrumental quality of contact between the self and the outside world, the individual may express his/her discontent towards the body and the The skin, on the other hand, serves as an artifact of contact between the self and the outside world. The choice of whether or not to express non suicidal self injury to the outside world is also based on the individual's and China's unique socio-cultural concepts. Influenced by the notion of “the skin of the body comes from the parents,” self-injured individuals may be too shy to express their grievances, or they may turn to their peers for help and influence the psychological state of their peers. This study explores the process of non-suicidal self-injury and its internal and external dynamics in order to provide some research perspectives on non-suicidal self-injury behavior.